Peran Penyuluh Pertanian Dalam Peningkatan Produktivitas Padi Melalui Transformasi Pertanian ( Studi Kasus di Kelurahan Tibojong Kecamatan Tanete Riattang Timur ) - Amin Jaya, Muhammad; Helda Ibrahim; Herman Nursaman; Syamsul Rahman (Jurnal KIRANA, 2025)
Bone Regency is known as one of the main rice-producing regions in South Sulawesi, with many of its residents dependent on the agricultural sector. East Tanete Riattang District is one of the areas in Bone Regency with significant agricultural potential. However, constraints such as limited farmer resources, lack of technology utilization, and conventional farming methods result in suboptimal harvests. Research Method: This study was conducted using a Likert Scale approach. The population of farmers in Tibojong Village, Tanete Riattang District, Bone Regency, is 250. The sample size represents 20% of the total population. The results indicate that agricultural extension workers play a crucial role in supporting agricultural transformation through training, mentoring, technology introduction, access to capital, and strengthening farmer groups. Their roles as motivators, innovators, dynamists, educators, and facilitators have been effectively implemented, as evidenced by an average score of 77.70% in the Strongly Agree category. They are also perceived to help farmers improve their morale, cooperation, skills, and market access.